(untitled) (Research, Society and Development, 2021)
Due to the growth of sheep breeding and the increase in demand for their products, there is the need to invest in the health of these animals. Thus, it becomes essential to use diagnostic tools for metabolic diseases like toxemia of pregnancy. This research aims to validate the diagnostic technique in reagent strip for β-hydroxybutyrate (BHB) in human portable glucose in sheep of Dorper and White Dorper. 111 otherwise healthy sheep, 79 of 32 Dorper and White Dorper were used in different production phases, which were empty (n=44), patients (n=37) and recently calved (n=30). Blood collection was performed by puncturing the jugular vein, with vacuum collection system, without anticoagulant tube. Instantly, was performed to determine the BHB test strip by the method of using the portable glucose meter. The determination of BHB in serum was performed in an automatic biochemical analyzer. Analysis, using the Kolmogorov-Smirnov test (p<0.05), there was a non-parametric distribution of the data, they are arranged in a paired manner, to which the same individual was examined by two techniques, the test was chosen McNemar to verify the difference between hypothesis testing. In addition, we performed the calculation of Kappa coefficient (95%) to check the reproducibility of the tests, combined with sensitivity and specificity calculations, considering the laboratory test as the gold standard. There was no significant difference between the results of dipstick to ketone bodies and biochemistry laboratory analysis, considering the total of 111 animals. In this analysis, the statistical resulted in a Kappa Index of 85%, with a sensitivity of the reagent strip 93% and specificity of 96%. In animals divided into different breeding groups, because there is no disagreement results, it is considered the Kappa index 100% and thus no possibility of calculating the sensitivity and specificity. This was only possible in newly calved classification of animals. In this category, the McNemar test (p=0.3173) with 95% demonstrated a Kappa coefficient 80.6%, with 93% sensitivity and 87% specificity. The recently calved sheep in this category groups have paired results and thus presented a Kappa coefficient of 80.6%, with 93% sensitivity and 87% specificity. The test reagent strip for β-hydroxybutyrate in human portable blood glucose meter is considered excellent and reliable and can be used as a diagnostic tool in sheep.